Who You Train Matters : Identifying Complementary Effects of Financial Education on Migrant Households - Doi, Yoko; McKenzie, David; Zia, Bilal (World Bank, Washington, DC, 2012)
There has long been a concern among policymakers that too much of remittances are consumed and too little saved, limiting the development impact of migration. Financial literacy programs have become an increasingly popular way to try and address this issue, but to date there is no evidence that they are effective in inducing savings among remittance-receiving households, nor is it clear whether such programs are best targeted at the migrant, the remittance receiver, or both. The authors conducted a randomized experiment in Indonesia which allocated migrants and their families to a control group, a migrant-only training group, a family member-only training group, and a training group in which both the migrant and a family member were trained. Three rounds of follow-up surveys are then used to measure impacts on the financial knowledge, behaviors, and remittance and savings outcomes of the remaining household. They find that training both the migrant and the family member together has large and significant impacts on knowledge, behaviors, and savings. Training the family member alone has some positive, but smaller effects, whilst training only the migrant leads to no impacts on the remaining family members. The results show that financial education can have large effects when provided at a teachable moment, but that this impact varies greatly with who receives training.